Self-efficacy, intention, and attitude toward human papillomavirus vaccination among urban females in indonesia: a cross-sectional study - Samaria, Dora; Desmawati, Desmawati; Mawaddah, Fauziah; Mizka, Nevin Zhasmin; Dwinova, Raras (Jurnal Ners, 2024)
Introduction: Women's choice to undergo vaccination against the Human Papillomavirus (HPV) is shaped by a multitude of factors. This study seeks to investigate the differences of intentions and attitudes toward the HPV vaccine and its effect size among women categorized into three groups based on their level of self-efficacy. Methods: As many as 441 respondents were selected using the consecutive sampling method. The samples were divided into three groups based on their level of self-efficacy (low, medium, and high). The research employed a cross-sectional design from 13 May to 15 June 2023 in the working area of Public Health Centers located in Jakarta by implementing individual home visits. The research instruments comprised the Self-Efficacy Scale for HPV vaccination, the Intentions to Receive the HPV Vaccine Questionnaire, and the Attitude of HPV, Cervical Cancer, and Vaccine HPV Questionnaire; all were declared valid and reliable. The Kruskal-Wallis Test, the Tukey HSD Post Hoc Test, and the Epsilon Squared Test were performed to examine intention and attitude based on the type of self-efficacy and the effect size found. Results: Significant differences were observed in intention (p<0.001) and attitude (p<0.001) among the three self-efficacy groups, demonstrating relatively robust effect sizes (attitude: Îµ2=0.109, p<0.001; intention: Îµ2=0.159, p<0.001). Conclusions:The research demonstrated discernible discrepancies in intention and attitude across the three sample groups distinguished by their self-efficacy levels. It is advisable to design interventions focusing on health promotion that highlight the diverse needs and characteristics of different groups of women.